REVIEW OF THE COMPLICATIONS IN PROSTHESIS MAKING & SERVICING - Chan, Wai Ti (Asian Journal Of Medical Technology, 2022)
Prostheses are intended to restore the human body's appearance and return some functions lost due to the loss of limbs. The prosthesis industry exists for this purpose, as well as the servicing of the prostheses. However, there are complications in the design and installation of prostheses, as well as servicing them. Prosthesis usage is subjected to the specific circumstances of the recipient and is dependent on medical coverage for long-term servicing. The relatively low number of cases involving prostheses compared to other medical cases and the circumstantial differences between these cases prevent in-depth and comprehensive studies of the industry, preventing the establishment of standardized best practices. Despite this, research and development of improvements for recipients' problems continue, utilizing the latest technologies to address technical complications. This article consolidates the present-day complications of prosthesis making and servicing.